2022
DOI: 10.1007/s40119-022-00271-9
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Coronary Plaque Features: A Narrative Review

Abstract: Advances in coronary plaque imaging over the last few decades have led to an increased interest in the identification of novel high-risk plaque features that are associated with cardiovascular events. Existing practices focus on risk stratification and lipid monitoring for primary and secondary prevention of cardiac events, which is limited by a lack of assessment and treatment of vulnerable plaque. In this review, we summarize the multitude of studies that have identified plaque, haemodynamic and patient fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Non-calcified plaque was defined as having an attenuation < 350 HU. Vulnerable high-risk plaque was defined as hypodense non-calcified plaque and/or positive remodelling index defined as the luminal diameter maximum stenosis divided by the luminal diameter in a proximal healthy segment > 1.10 [30] .…”
Section: Methodsmentioning
confidence: 99%
“…Non-calcified plaque was defined as having an attenuation < 350 HU. Vulnerable high-risk plaque was defined as hypodense non-calcified plaque and/or positive remodelling index defined as the luminal diameter maximum stenosis divided by the luminal diameter in a proximal healthy segment > 1.10 [30] .…”
Section: Methodsmentioning
confidence: 99%
“…59 Multiple studies have demonstrated that CCTA is able to detect plaque features associated with ACS risk. 58,61 Yuvaraj et al matched 41 patients with stable CAD presenting with HRP on CCTA to 41 patients without HRP. They found that RCA-based PCAT MA was higher in patients with HRP than in patients without (−80.7HU ± 6.50 vs −84.2HU ± 8.09 p = 0.03).…”
Section: Pcat As a Cad Biomarkermentioning
confidence: 99%
“…HRP are prone to rupture and exhibit positive remodeling without significant lumen narrowing. Standard imaging methods may not accurately assess nonobstructive, but high-risk, plaques [83]. However, innovative approaches using 18F-sodium fluoride (18F-NaF) positron emission tomography (PET) uptake and PCAT attenuation on CT have shown promise [84][85][86].…”
Section: Correlation Between Pcat Plaque Vulnerability and Acsmentioning
confidence: 99%